Relevansi Pemikiran Imam Al-Ghazzali Tentang Interaksi Edukatif Pendidik Dan Peserta Didik Terhadap Pendidikan Di Era Modern - Sona Fathurohman (Jurnal Inovasi Global, 2025)
Imam Al-Ghazali, a prominent Islamic scholar and philosopher, is known for his significant contributions to various fields of science, including education. His thoughts on educational interaction between educators and students offer a perspective that is still relevant to be analyzed and applied in the context of modern education. Given the challenges and dynamics that continue to develop in the era of globalization and digitalization, it is important to explore how Al-Ghazali's educational principles can be adapted and implemented in the Education system in the Modern Era. This article aims to examine in depth Al-Ghazali's Thoughts on the educational interaction of Educators and Students to Education in the Modern Era. This study is in the form of library research using the content analysis method to find the Relevance of Imam Al-Ghazali's Thoughts on the Educational Interaction of Educators and Students to Education in the Modern Era. The results of this study conclude that Imam Al-Ghazali made a major contribution through his thoughts in Ihya' al-Ulum ad-Din, which emphasizes the importance of educational interaction between teachers and students. Imam Al-Ghazali taught the importance of education that not only includes intellectual aspects, but also the formation of noble morals through a deep educational process of teaching and learning. Educational interaction is a reciprocal relationship that occurs between teachers and students, which is oriented towards achieving educational goals. It contains two main elements: deliberate and planned communication, and the goal of leading students towards maturity and character formation. In the learning process, educational interaction not only conveys material, but also instills noble values and attitudes in students. In the midst of globalization and materialism that influence the world of education, it is important to restore ethical and spiritual values based on religion in educational interaction.